Reaktualisasi Corak Tafsir Adab Al-Ijtima’i Terhadap Persoalan Sosial Kemasyarakatan Dan Perkembangan Zaman - Bustami Saladin (UIN Mataram, 2020)
This study explains the relevance of tafsir adab al-ijtima’iy regarding the social change and answering the future. This article focus on Muhammad Abduh’s thought about tafsir adab al ijtima’iy and compared with several Muslim thinkers thought about this subject. Muhammad ʻAbduh's interpretation of the verses of the Qur'an uses a beautiful, easy language style that can be accepted by all levels and complements it with social relevance. The interpretation is known as tafsir adab al-Ijtima'i. This article aims to introduce the style of interpretation of al-Ijtimâi adab as an alternative to re-actualization of the principal values ​​of the Koran, focused on Muhammad Abduh as a representation of tafsir adab al-ijtima’iy styles of interpretation.